Endophytic community in juvenile Acer pseudoplatanus and pathogenicity of Cryptostroma corticale and other associated fungi under controlled conditions - Bußkamp, Johanna; Bien, Steffen; Neumann, Leonard; Blumenstein, Kathrin; Terhonen, Eeva; Langer, Gitta Jutta (Springer Science and Business Media LLC, 2024)
The causative agent of sooty bark disease, Cryptostroma corticale, has, for some years, caused increased damage to maples (Acer spp.) in Germany and throughout Europe. It has been stated that this pathogen can occur latently in Acer. In this study, the composition of endophytic fungi of woody stem tissues of sycamore (Acer pseudoplatanus) saplings were analysed in order to investigate whether C. corticale is present in young, visually healthy maple trees from natural regeneration. The most abundant taxa of the 30 isolated endophytes were Diaporthe cf. rudis and Petrakia irregularis. An association of five fungal species (Biscogniauxia mediterranea, Coniochaeta velutina, Gibellulopsis catenata, Neocucurbitaria quercina, Tangerinosporium thalitricola) with A. pseudoplatanus was reported for the first time. Cryptostroma corticale was not present in the juvenile sycamore stems. Furthermore, its pathogenicity was studied in comparison to other pathogens associated with A. pseudoplatanus, namely Diplodia mutila, Dothiorella sp., Nectria cinnabarina, Neonectria coccinea, Neonectria punicea and Stegonsporium pyriforme. The longest necroses were induced by C. corticale followed by N. coccinea. In a trial with a C. corticale spore suspension sprayed directly on stem bark, the fungus could be re-isolated from woody tissue, however necroses were evoked only when the bark was wounded prior to infection. The results from the experiments presented here function as additional evidence for the ability of C. corticale to establish endophytically within the host and, in particular, for the ability of the fungus to establish a successful infection/entrance through intact bark.
Keywords: fungal endophytes; pathogenicity tests; sooty bark disease; sycamore maple; aggressiveness; infection pathway